Optimalisasi Peran Dinas Sosial dalam Pemberdayaan Anak Jalanan di Kota Samarinda - Dyna Rodhiah Azizah; Budiman, Budiman (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This study aims to understand and describe the Optimization of the Social Affairs Office's Role in Empowering Street Children in Samarinda City. This research focuses on the government's efforts, specifically the Social Affairs and Community Empowerment Agency of Samarinda City, in addressing issues faced by Individuals with Social Welfare Problems (PMKS), particularly street children, through policy programs outlined in the Samarinda City Social Affairs Office's Key Performance Indicators for the years 2022-2026. It also focuses on the factors hindering the efforts of the Samarinda City Social Affairs Office in addressing the number of street children. The data collection technique used is purposive sampling. The results of this research indicate that the implementation of the role of the Social Affairs and Community Empowerment Office in addressing the issue of street children in Samarinda City has been carried out to the best of their abilities in accordance with Samarinda City Regional Regulation No. 07 of 2017 concerning Guidance for Beggars, Street Children, and Homeless People. Efforts include preventive coaching, continued coaching, social rehabilitation as a form of protection, and providing assistance. However, there are inhibiting factors experienced by the office in addressing the issue of active street children, particularly the difficulty in controlling them and prohibiting their activities on the streets.